2020
DOI: 10.1021/acs.langmuir.0c01942
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Protein Immobilization and Stability on Heterogeneous C–TiO2 Hybrid Nanostructures: A Single Protein AFM Study

Abstract: Enhancing molecular interaction is critical for improving the immobilization and stability of proteins on TiO 2 surfaces. In this work, mesoporous TiO 2 materials with varied pore geometries were decorated with phenyl phosphoric acid (PPA), followed by a thermal treatment to obtain chemically heterogeneous C−TiO 2 samples without changing the geometry and crystalline structure, which can keep the advantages of both carbon and TiO 2 . The molecular interaction force between the protein and the surfaces was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…Regulating active substrates is often used to enhance the sensitivity (i.e., intensity) and selectivity for trace detection, especially for the semiconductor-based SERS techniques , with a low SERS intensity. Methods such as metal doping, use of composites, , as well as structure optimization and modification , have been used to increase the SERS intensity. Intrinsically, the SERS intensity is strongly related to the interactions among the adsorbed molecules and their electron-transfer ability, implying that regulating them is essential to improve the enhancement and to lower the limit of detection.…”
Section: Introductionmentioning
confidence: 99%
“…Regulating active substrates is often used to enhance the sensitivity (i.e., intensity) and selectivity for trace detection, especially for the semiconductor-based SERS techniques , with a low SERS intensity. Methods such as metal doping, use of composites, , as well as structure optimization and modification , have been used to increase the SERS intensity. Intrinsically, the SERS intensity is strongly related to the interactions among the adsorbed molecules and their electron-transfer ability, implying that regulating them is essential to improve the enhancement and to lower the limit of detection.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of surface chemistry on the stability and activity of immobilized proteins is critical in many fields, including biosensing, drug delivery and biofuel cells [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] . Because of this influence, the immobilization of proteins has been investigated using a variety of support materials, as for example gold [9] , [10] , silica [11] , [12] , carbon nanotubes [13] , [14] , graphene [15] , [16] , and self-assembled monolayers [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, determination of the strength of the interactions on the macroscale using adsorption capacity measures and electrical signals is not adequate. Instead, microscale measures using, for example, atomic force microscopy (AFM)-based methods enable quantification of the force between single protein molecules and the substrate surface [2] , [19] , [20] , [21] , [22] , [23] , even though identification of the key microscopic features affecting the stability of the immobilized protein is not possible.…”
Section: Introductionmentioning
confidence: 99%
“…), finding that these molecular forces depend both on the properties of the protein and the solid surface and the pH conditions but not the surface roughness. Importantly, these determined molecular forces can be further used as a guideline to design the macroscopic experiments, including protein separation measured by high-performance liquid chromatography, surface-enhanced Raman scattering (SERS)-based protein biodetection, and electron transfer ability of the enzyme tested using an electrochemical biosensor . We found that the magnitude of the ionic strength, induced by the buffer ions, significantly alters the interfacial process performance, while how the ionic strength affects the molecular interaction at the microscale and then influences the performance at the macroscale has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%